"I have ideas but I don't want to say them aloud." Employee-driven innovation discourses at a retail chain store. (2016) - Hiltunen, Esa; Henttonen, Kaisa
This intensive case study explores employee-driven innovation discourses at a Finnish retail chain hypermarket. This study area is of importance because employee-driven innovation management has not been studied in-depth before in the retail sector. This single-case study focused on one individual who considered herself to be an innovator and possessed a special desire to develop and renew daily activities in a retail store. Discourse analysis, as a methodological approach, shows how innovation discourse is divided into two main repertoires: individualistic and realistic innovation repertoires. The study contributes to new contextualised knowledge on innovation management and employee-driven innovation research. It provides understanding of how leaders could support participation in innovation activity at the frontline level, especially in the ideation phase.